Inclusión educativa en el contexto chileno: breve recorrido histórico (Revista Electrónica Diálogos Educativos. REDE, 2026)
The main objective of this article is to relate the concept of inclusion contained in national and international regulations in the field of education, as well as in the current updated literature, with the scope of the concept of exclusion as an element that hinders the inclusive process. This study is carried out based on a bibliographic compilation of the underlying concepts, starting with their origin and evolution, as well as a documentary analysis of current educational policy related to inclusion, in view of the particular concept that has been included in Chilean regulations since 2009. In analytical terms, reflections are presented and placed under tension based on the challenges that persist and that, at the same time, must be made visible, considered, and examined, with the aim of supporting progress toward educational inclusion in the Chilean context, without losing sight of the relevance of raising awareness of exclusion in the educational sphere for achieving the goals proposed in the national and international educational agenda. Finally, exclusion is considered an aspect that must be overcome in order to facilitate the transition toward inclusive, quality education as a guarantor of the right to learning for all those who participate in the school context.Keywords: Education, Inclusive education, Educational exclusion, Educational policy.